(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
In recent years, there has been a change of scientific paradigms in world linguistics, and now the anthropocentric paradigm has come to the center of attention of linguists. At the end of the last century, pragmalinguistics developed as one of the directions of anthropocentric linguistics. Pragmalinguistics is a branch of modern linguistics that studies the possibilities of language units arising from a number of factors, such as situation, context, general knowledge of language speakers about the object of speech. Among such problems of linguistics in world linguistics, it is important to study women’s speech, to reveal its pragmatic features, to study the peculiarities of the expression of connotative meaning in women’s speech. These issues are discussed in this article based on examples of fiction.